Miscellaneous early dynastic and Sargonic texts in the Cornell University collections - Bartash, Vitali (Cornell University studies in Assyriology and Sumerology, 2013)
I -Texts from the Umma Region -- I.1 -- Administrative -- Early dynastic iiia -- Early dynastic iiib -- Early Sargonic -- Early to middle Sargonic -- Classical Sargonic -- I.2 -- legal -- I.3 -- Mathematical -- I.4 -- School/exercise -- Texts from Adab -- Ii.1 -- Administrative -- Early dynastic iiia/b -- Early dynastic to early Sargonic -- Early Sargonic -- Early to middle Sargonic -- Middle Sargonic -- Middle to classical Sargonic -- Classical Sargonic -- Late Sargonic -- Ii.2 -- bulla -- Ii.3 -- legal -- Ii.4 -- letter -- Texts of uncertain provenance -- Iii.1 -- Administrative texts -- Early dynastic -- Early Sargonic -- Middle to classical Sargonic -- Classical Sargonic -- Late Sargonic -- Iii.2 -- mathematical -- Iii.3 -- royal/monumental -- Iii.4 -- school/exercise